(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article analyzes the key mechanisms of state policy in eliminating emergency environmental situations, existing challenges, and possible solutions. The role of state policy in ensuring environmental security, legal and economic mechanisms, international experience, and innovative approaches are examined. The research findings have both scientific and practical significance for improving strategies to combat emergency environmental situations.